A comparison of 5 or 7 days of rabeprazole triple therapy for eradication of Helicobacter pylori (Faculty of Medicine Universitas Indonesia, 2010)
Aim A combination of PPI and 1000 mg amoxicillin/500 mg clarithromycin twice daily for 2 weeks has been proven effective in the eradication of H. pylori. Most studies suggested that treatment for 7 and 10 days may be equally effective. Few data are available on the efficacy of 5-day triple therapy. Aim of this study was to compare 5-day and 7-day rabeprazole triple therapy for eradication of H. pylori infection. Methods We prospectively studied 60 consecutive H. pylori-infected patients who came to hospitals in six centres in Indonesia and who underwent upper endoscopy and biopsy. H. pylori infection was confirmed if two rapid urease tests (Pronto Dry) and histology or urea breath test were positive. Patients were assigned to either an open-labelled 5-day or 7-day course of oral amoxicillin 1000 mg b.i.d., clarithromycin 500 mg b.i.d., and rabeprazole 10 mg b.i.d. (RAC). Four weeks after therapy, all patients had a repeated UBT for evaluation of the presence of H. pylori. Results Of the 60 patients (42 males and 18 females) with mean age (± SD) 47.63 ± 13.93 years, range 21-74 years, 25 patients (41.7%) had 5-day treatment and 35 patients (58.3%) had 7-day treatment. With 5-day treatment, 18 patients (72%) and with 7-day treatment 32 patients (91.4%) became negative for H. pylori infection. The eradication failure was found on 7 patients (28.0%) in 5-day treatment and 3 patients (8.6%) in 7-day treatment. Conclusions The study showed that the eradication of H. pylori infection by triple rabeprazole-based treatment in 7-day is still better than in 5-day. (Med J Indones 2010; 19:113-7)